The Role of Technology in Plant-Inspired Art and Creativity - J. JOY PRINCY & M. NATARAJAN (Journal of Dharma, 2025)
This article investigates the relationship between technology, plant life, and artistic creativity within the emerging field of plant humanities. Employing a qualitative interpretive methodology grounded in ecocriticism, post humanist theory, and environmental aesthetics, the study analyses contemporary techno-botanical artistic practices including biosensing installations, augmented reality applications, and immersive digital environments. The article proposes a three-stage conceptual framework—disconnection, reconciliation, and balance—to explain how digital technologies reshape contemporary human–plant relationships. Through critical analysis of selected digital artworks and environmental media, the study demonstrates that technological mediation can both distance humans from ecological experience and create new forms of multispecies awareness. The findings suggest that technology need not be inherently opposed to environmental consciousness; rather, when ethically and creatively applied, it can foster deeper ecological perception and engagement with plant life. The article therefore contributes to plant humanities by offering a conceptual model for analyzing techno-botanical aesthetics in the Anthropocene.